2019
DOI: 10.1021/acsenergylett.9b00414
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Doped NiOx as an Effective Hole-Selective Layer for a High-Performance Sb2Se3 Photocathode for Photoelectrochemical Water Splitting

Abstract: Although antimony triselenide (Sb2Se3) has been intensively investigated as a low-cost p-type semiconductor for photoelectrochemical (PEC) water splitting, most previous studies focused on only the top interface of Sb2Se3 photocathodes. Herein, a solution-processed Cu-doped NiO x (Cu:NiO x ) thin film is proposed as an effective bottom contact layer for the Sb2Se3 photocathode. The photocurrent density of the Sb2Se3 photocathode is improved to a record-high level of 17.5 mA cm–2 upon the insertion of Cu:NiO x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 48 publications
(94 reference statements)
1
80
0
Order By: Relevance
“…successive depositions at 340 and 460°C followed by cooling the chamber naturally after deposition). The role of the Au layer in Sb 2 Se 3 photoelectrodes, which facilitates the transfer of photo-generated holes, has been discussed in previous reports on Sb 2 Se 3 for PEC water splitting 26,32 and thin-film solar cells 33 . Despite the filmtype morphology, there were some pin-holes resulting in exposure of the substrate (red circles in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…successive depositions at 340 and 460°C followed by cooling the chamber naturally after deposition). The role of the Au layer in Sb 2 Se 3 photoelectrodes, which facilitates the transfer of photo-generated holes, has been discussed in previous reports on Sb 2 Se 3 for PEC water splitting 26,32 and thin-film solar cells 33 . Despite the filmtype morphology, there were some pin-holes resulting in exposure of the substrate (red circles in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It has also been reported that Sb 2 Se 3 is intrinsically stable towards photocorrosion in strong acidic media unlike Cu 2 O, which is vulnerable to photocorroson 22 . Owing to these merits, the photocurrent density of the Sb 2 Se 3 photocathode has improved rapidly from the initially reported value of 2.5 mA cm −2 to 17.5 cm −2 at 0 V against the reversible hydrogen electrode (RHE) over the short period of its development [23][24][25][26] . However, it is still far below the theoretical maximum (about 40 mA cm −2 , assuming a 1.2 eV E g and a 100% incident photon-to-current efficiency (IPCE)).…”
mentioning
confidence: 99%
“…6B) with onsets comparable to the very best reports in the literature. [49][50][51] Furthermore, the large dark current observed in the Sb 2 Se 3 /TiO 2 device is suppressed when a dipole layer is utilized (Fig. 6A, dotted lines).…”
Section: Improvement Of Emerging Materials Thin Film Devicesmentioning
confidence: 89%
“…In a strongly acidic electrolyte (1 m H 2 SO 4 , pH ≈ 1), Sb 2 Se 3 thin film prepared with the selenization of electrodeposited Sb and Pt cocatalyst further improves the photocurrent density to 16 mA cm −2 at 0 V RHE . By introducing a Cu‐doped NiO x hole‐selective layer as an effective bottom contact layer for a solution‐processed Sb 2 Se 3 photocathode, a record photocurrent density of 17.5 mA cm −2 at 0 V RHE in acidic electrolytes is achieved …”
Section: Introductionmentioning
confidence: 99%